INVESTMENT TECH: THE RISE OF DISCOUNT BROKERS IN INDIA - Jawa, Dr. Rachna; Kabra, Rahul; Aggarwal, Ria (International Journal of Research -GRANTHAALAYAH, 2022)
This paper analyzes the emergence of discount retail investment platforms in India which have disrupted the Fintech landscape of the country, especially for the traditional brokerages, by presenting a technologically cost-efficient solution to the general public. Through this expository paper, the aim is to highlight the rising prominence of discount brokerages and their role in revolutionizing the Indian stock market. This analytical study endeavours to decipher the key reasons for the shift of retail investors to discount brokers recently and uses time-series data from 2013-14 to 2020-21 to gauge the strength of the relationship between mobile and internet-based trading and the broking leaders, like Zerodha.